Photobiomodulation changes type 1 collagen gene expression by pulp fibroblasts. (3rd May 2018) - Vitor, Luciana Lourenço Ribeiro; Prado, Mariel Tavares Oliveira; Neto, Natalino Lourenço; de Oliveira, Rodrigo Cardoso; Santos, Carlos Ferreira; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini
Abstract: This study aimed to evaluate type 1 collagen (COL1) gene expression by human pulp fibroblasts from primary teeth (HPF) after the variation of photobiomodulation (PBM) parameters. HPF were obtained from a biorepository, used at 4th passage, and irradiated (InGaAlP—660 nm) varying the power and application time according to the following groups: G1: 1.2 J cm −2 –05 mW–10 s; G2: 2.5 J cm −2 –05 mW–20 s; G3: 3.7 J cm −2 –05 mW–30 s; G4: 5.0 J cm −2 –05 mW–40 s; G5: 6.2 J cm −2 –05 mW–50 s; G6: 2.5 J cm −2 –10 mW–10 s; G7: 3.7 J cm −2 –15 mW–10 s; G8: 5.0 J cm −2 –20 mW–10 s; G9: 6.2 J cm −2 –25 mW–10 s. The control group (G10) was not irradiated and maintained with DMEM + 10% SFB. RT-PCR was used to evaluate COL1 gene expression at 6, 12, and 24 h after irradiation. Intra- and intergroup comparisons were performed by two-way ANOVA followed by Tukey test (p < 0.05). The intragroup comparison showed statistically significant differences among periods (p < 0.05). In G1, G9, and G10 higher COL1 gene expression occurred at 12 h (p = 0.07), while in G2 to G8, the peak of higher expression occurred at 6 h (p = 0.02). The intergroup comparison did not show statistically significant differences (p > 0.05). The energy densities from 2.5 to 5 J cm −2, regardless of the variation in PBM parameters, biomodulated the COL1 gene expression. At the energy density of 6.2 J cm −2, longer application time and smaller power changed the pattern of COL1 gene expression by pulp fibroblasts from human primary teeth.